TRANSFORMATION OF THE GLOBAL INSURANCE MARKET IN THE CONTEXT OF THE INTRODUCTION OF NEW BUSINESS MODELS AND MODERN INSURANCE TECHNOLOGIES (World of finance, 2024)
Introduction. The insurance industry has undergone significant changes in the last decade. Global transformations in society, rapid development of financial technologies, systemic financial shocks and the coronavirus pandemic, escalation of military conflicts into war, necessitate a rethinking of the conceptual foundations of insurance activities, modification of relationships between participants in the insurance market, and the testing of new business models for insurance companies. In this context, the study of current trends and the development of directions for further transformation of the global and local insurance markets in the context of optimizing the business processes of insurance companies in the global InsurTech environment become particularly important.The purpose of the article is to analyze the realities of the functioning of the global insurance market in the conditions of changing the paradigm of its development; to identify key challenges, identify new threats, and outline the main vectors of transformation of the insurance business environment in the modern InsurTech space.Results. The decisive role of the insurance market in providing insurance protection to economic entities, individuals, and international institutions has been clarified; macroeconomic uncertainty and geopolitical transformations that significantly affect the development of local and global insurance markets have been identified. It has been proven that the insurance business has demonstrated its adaptability to new realities of functioning by improving operational systems, applying innovative strategies and digital marketing technologies, implementing new financial solutions, and establishing strategic partnerships. New vectors of development of the insurance market in the global insurance space have been identified, aimed at introducing InsurTech and automating business processes in the activities of insurers; a customer-oriented approach in working with policyholders; and the development of new insurance products taking into account their hyper-personalization and accessibility.Conclusions. The following conclusions have been drawn based on the results of the study: new trends in the transformation and modernization of the insurance market are observed in the context of the implementation of innovative technological achievements, the formation of strategic alliances between insurance companies and other financial structures; intensive shifts in the insurance business are taking place in a regional context, particularly in Asian and other developing countries; insurance companies are being reprofiled towards a customer-oriented business model, digital marketing, remote customer service, and the promotion of new insurance products.